Quality assessment of imported powder milk at Mansoura city, Egypt - Abdelkhalek, Adel; Elsherbini, Mohammed; Eletriby, Dalia; Sadak, Ahmed (Journal of Advanced Veterinary and Animal Research, 2016)
Objectives: The objective of this study was to assess the keeping quality of powder milk sold at local markets in Mansoura City, Egypt, and to isolate the contaminated bacteria particularly Salmonella spp., E. coli and Staphylococcus aureus from these milk samples. Materials and methods: A total of 50 powder milk samples were collected from different sources at Mansoura, Egypt. The samples were subjected for physical examination to determine their pH and acidity. Microbiologcal assessment of the samples were done by Total Bacterial Count (TBC), Total Coliform Count (TCC), True fecal E. coli count, and Most Probable Number (MPN), and Total mold and yeast count. Results: Minimum and maximum values of TBC were 0.45×102 cfu/gm and 5.11×103 cfu/gm milk powder, respectively. On the other hand, minimum and maximum values of fungal count were 0.08×102/gm and 2×102/gm samples, respectively. No E. coli and Salmonella spp. could be isolated from the samples. However, 18% (n=9/50) samples were found to be contaminated with Staph. aureus. Conclusion: Based on the Egyptian Standards, the samples were satisfactory in terms of the association of Salmonella spp., E. coli, and fungi. Contamination with Staph. aureus warrans the public health. Thus, appropriate care and preventive measures are suggested. http://dx.doi.org/10.5455/javar.2016.c122